A review of the effects of forest management intensity on ecosystem services for northern European temperate forests with a focus on the UK. (10th October 2017) - Sing, Louise; Metzger, Marc J; Paterson, James S; Ray, Duncan
Abstract: Ecosystem services (ES) are the benefits that people receive from ecosystems. Understanding the impact of forest management on their supply can inform policy and practice for meeting societal demand. The objectives of this paper are to identify and review the effect of management intensity on priority ES supply and identify synergies and trade-offs among ES of different management approaches. We review seven priority ES identified from UK land and forestry strategy and policy documents: timber/biomass production, carbon storage, biodiversity, health and recreation, water supply and quality and flood protection. We present a synthesis of the impact of management on relative ES supply. It shows that low intensity management is unsuitable for high biomass production, yet provides high or moderately high levels of other services. Higher intensity management impacts negatively on biodiversity, health and recreation and water supply services. Combined objective forestry provides high or moderately high levels for all services except biomass. We recommend that a diversity of management approaches is needed to maintain multiple ecosystem service provision. The ES framework offers opportunities to forest management by revealing areas of conflict or co-production and potential trade-offs that may arise from adjusting management intensity.